Simulation of linear dynamic macro model of photo catalytic sensor in SPICE. (2014) - ,; ,
Abstract : Purpose – The flow injection analysis (FIA) technique by Yoon‐Chang Kim et al. for the determination of chemical oxygen demand (COD) involves the complete analysis including sampling and washing. FIA is analytical method for the measurement of COD using photochemical column. This method uses a bulky setup and takes 10‐15 minutes to get the output result which is a tedious and time‐consuming job. If conventional method is continuously used for a long time, then it is stable only for 15 days. The purpose of this paper is to propose an approach which is more users friendly and fast in operation by modeling and optimization of sensor used for water quality monitoring. This is to overcome several drawbacks generally found in the previous work like complex designing, nonlinearity and long computation time. The nonlinearity in conventional device is overcome by increasing the values of coefficient of determination R 2 which in turn reduce the standard error.Design/methodology/approach – A simulation program with integrated circuit emphasis (SPICE) model of photo catalytic sensor (PCS) is proposed for easy and fast operation and optimization of power.Findings – The proposed macro model operates under subthreshold conditions that are appreciated in large integrated system design. The results of simulation were found to be fairly in agreement with the theoretical predictions. The results exhibited near linear variations of parameters of interest with appreciably reduced response time. The coefficient of determination ( R 2 ) has been found to be more in this technique.Research limitations/implications – As the threshold voltage of different photo catalytic materials will be different, Eref in the setup has to be adjusted accordingly to obtain sufficient quantity of current to operate the device.Originality/value – This approach relies on the SPICE model. The development of SPICE model for photochemical sensor is novel which is fast in operation and more user friendly.